South Africa Economic Update : Focus on Export Competitiveness - World Bank (Washington, DC, 2014)
In its National Development Plan 2030 and its New Growth Path (2011), South Africa identifies the export sector as an engine for faster, more inclusive, and job-intensive growth. The National Development Plan is targeting export volume growth of 6 percent a year, to achieve an annual increase in real Gross Domestic Product, or GDP growth of about 5.5 percent and to help generate 11 million new jobs by 2030. Despite successes in some subsectors, South Africa will need to greatly improve its export performance to meet these targets. The report highlights opportunities for growth, particularly with Sub-Saharan Africa being the largest market for non-mineral exports. It also explores strategic directions that can ignite export growth and help South Africa realize its goals of creating jobs and reducing poverty and inequality.